DEVELOPMENT OF IONIC LIQUID MODIFIED SILICA SYNTHESIS INCORPORATED INTO THIN FILM COMPOSITE MEMBRANE - PUSHPANATHAN, THULASI (IRC, 2019)
Separation technology using polymeric membrane has been one of the potential strategies to effectively and cost efficiently to separate carbon dioxide (CO2). However due to trade off limitation between permeability and selectivity in polymeric membrane, thiswork fabricated Mixed Matric Membrane (MMM) compromising Pebax and 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate [EMIM][CF3SO3] ionic liquid (IL)modifiedsilica (SiO2) nanoparticles.To investigate the membrane structure various analysis including FESEM, TGA, DSC and FTIR are performed. CO2and CH4permeability and CO2/CH4 selectivity are measured for all membranes at different pressures from 2 to 10 bar.The cross section FESEM images showed interaction between polymer and particles has disrupted the polymer chain packing structure. The FTIR test confirmed that the IL modified silica nanoparticle has successfully blended into the polymer membrane. TGA and DSC results showed acceptable thermal resistance of all membranes. Membranes permeability increased with increase in particles loading percent due to high porosityof particles and high adsorption capacity especially for CO2 molecules. The highest CO2 permeability and CO2/CH4 selectivity was belong to PEBAX/IL modified silica 1wt.% membrane which was 127.54 and 49.63 GPU. All membranes showed permeability and selectivity growth from 2 to 10 bar.